2014
DOI: 10.4236/oje.2014.44018
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Phenology of the Braconid Community (Hymenoptera: Braconidae) in the Mediterranean Protected Landscape of Sierra Calderona (Spain)

Abstract: How to cite this paper: Falcó-Garí, J.V., et al. (2014) Diversity and Phenology of the Braconid Community (Hymenoptera: AbstractThe diversity of the Braconidae subfamilies (Hymenoptera) in the protected landscape of the Natural Park of Sierra Calderona (Eastern Spain) is analysed. Samplings have been carried out along 2010 in three different habitats: almond crop, Oak forest (Quercus suber L.) and Pine forest (Pinus halepensis Miller). In total, 2166 braconid specimens, belonging to 23 subfamilies, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…In addition, the phenological analysis showed that Opiinae species could be found in high altitudes from April to September being the highest abundance and diversity on August and September when weather conditions are better. These results are similar that ones found by Jiménez-Peydró & Peris-Felipo (2011) or Falcó-Garí et al (2014 in continental and Mediterranean forests, where the most abundant period was from May to August, coinciding with the greatest herbaceous diversity.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the phenological analysis showed that Opiinae species could be found in high altitudes from April to September being the highest abundance and diversity on August and September when weather conditions are better. These results are similar that ones found by Jiménez-Peydró & Peris-Felipo (2011) or Falcó-Garí et al (2014 in continental and Mediterranean forests, where the most abundant period was from May to August, coinciding with the greatest herbaceous diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Semakin banyak vegetasi bawah yang terdapat di dalam suatu eksositem, maka semakin banyak pula sumber nutrisi dan inang alternatif yang dapat digunakan oleh parasitoid untuk dapat melangsungkan kehidupannya. Pada perkebunan yang terdapat tanaman vegetasi lantai yang melimpah, terutama tanaman berbunga, baik tanaman yang tumbuh liar maupun sengaja ditanam, dapat menjadi faktor salah satu tingginya keanekaragaman parasitoid pada suatu ekosistem (Falco-Gari et al, 2014). Walaupun pengelolaan yang ideal adalah dengan mengendalikan vegetasi lantai pada suatu perkebunan, tetapi suatu perusahaan, terutama perkebunan, tentunya tidak ingin ada kompetisi pada produk utamanya.…”
Section: Pembahasan Keanekaragaman Hymenoptera Parasitoidunclassified
“…Although many diversity studies around Braconidae have been carried out worldwide, for example in Brazil (Cirelli and Penteado-Dias 2003, Scatolini and Penteado-Dias 2003), Venezuela (Briceño et al 2007, Briceño et al 2009) or in the Iberian Peninsula (Andorra, Spain and Portugal) (Falcó-Garí et al 2006, Jiménez-Peydró and Peris-Felipo 2011, Peris-Felipo and Jiménez-Peydró 2011, Falcó-Garí et al 2014), these communities have been insufficiently analysed. However, in recent years, some biodiversity studies have been carried out.…”
Section: Introductionmentioning
confidence: 99%